AtomServ architecture: Towards internet-scaled service, publish, subscription, and discovery - Wu, Chen; Chang, Elizabeth (IEEE, 2006)
With the surge of SOA-based infrastructure and applications, increasingly end users and small-medium-enterprises directly participate in the service publish and discovery across the Internet. The recent shutdown of public UDDI exposes critical problems of existing Internet-based service discovery. Hence, public service discovery becomes a central SOA issue. In this paper, we present a light weight service discovery architecture built upon widely-adopted WWW technologies and proven software architectural styles. Firstly, it provides a handy discovery facility for personal web services providers and consumers, who would not be expected to able to use complex UDDI specifications with dedicated endpoint computing capability. Secondly, it widens the adoption of service discovery by allowing simple and uniform web user interfaces (e.g. Internet Explorer7.0 and Firefox1.1) to subscribe and access frequently changing business services. This undoubtedly lowers the entry barrier for end users to play the role of service providers or consumers in a sheer Service-Oriented Environment across the Internet.